Muslim textualities : a literary approach to feminism - Kane, Jean (New Delhi Routledge, 2022)
"In the first decade of the twenty-first century, Muslim women writers located in Europe and American entered the cultural mainstream. In literary and visual productions, the authors negotiated static visual emblems of Islam, most prominently as "the veil." They did so not by rejecting veiling practices, but by devising strategies of representation that drew on Muslim resources, concepts. and visual traditions as well as popular empowerment narratives. Mainstream reception of their works has often overlooked or misread the negotiations and tactics of these productions. Muslim Textualities argues for more flexible and capacious interpretation, with particular attention to visibility as a metaphor for political agency and to knowledge of cultural contexts. This provocative volume aims to articulate the Muslim female agency through clear and accessible analysis of the theory and concepts driving the interpretation of these works. Scholars interested in the working representations of Muslim women, feminist subjectivities, and the complexities of gender roles, patriarchy, and feminism in Islamic narratives will find this volume of particular interest"--
Includes bibliographical references and index.
Keywords: American literature; American literature; American literature; European literature; European literature; European literature; Women in literature; Feminism in literature